Disorders of Phosphate Metabolism: Hypophosphatemia and Hyperphosphatemia - Tinawi, Mohammad (Archives of Clinical and Biomedical Research, 2021)
Phosphorus in the body exists as phosphate. Phosphate is the most abundant intracellular anion and exists mostly as organic phosphate compounds critical to cellular functions such as adenosine triphosphate (ATP). The kidneys are the main regulator of phosphate homeostasis. There are three hormonal systems responsible for phosphate homeostasis, the parathyroid hormone (PTH), Fibroblast growth factor-23 (FGF-23)/klotho, and 1,25 dihydroxyvitamin D3 (1,25 (OH)2D3, calcitriol). Most cases of hypophosphatemia are acquired and are due to malnutrition as in alcoholism. The kidneys maintain phosphate level in the normal range; therefore, hyperphosphatemia is uncommon until glomerular filtration rate (GFR) falls below 30 ml/min. Hyperphosphatemia is common in patients on renal replacement therapy and is treated with dietary phosphate restriction, and phosphate binders.